Implementation of Haversine Algorithm in Web-Based Online Attendance Application - Wijaya, Leon Fernando; Tony, Tony (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2024)
Attendance is an important aspect of the world of work. A manual attendance system is a conventional attendance recording method that is still widely used. However, with the rapid advancement of technology, digital attendance now allows recording attendance through software connected to the internet. PT Password Solusi Sistem, as an information technology solution provider and system integrator, already has an online attendance application, but its effectiveness is still limited, and feature customization is difficult because the application comes from an external service provider. This research aims to develop a web-based online attendance application with the implementation of the Haversine algorithm to calculate the distance between the user’s location and the office location through geolocation technology during attendance so that the results of this calculation are used to provide information on attendance whether it is done outside or within the office radius. In addition, this study also compared the results of distance calculations between the Haversine algorithm and the Google Geometry Library in 20 different locations, which resulted in a difference of 0.0113. GPS Geolocation testing, conducted using a smartphone, showed 100% accuracy, with all test locations being valid. The results showed that the online attendance application with the Haversine algorithm was successfully implemented, and the accuracy comparison between the Haversine algorithm and Google Geometry Library showed almost similar results.